1998
DOI: 10.1002/jor.1100160612
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion and reliability of interfaces in cemented total joint arthroplasties

Abstract: Debonding of the prosthetic/polymethylmethacrylate interface has been implicated in the initial failure process of cemented total hip arthroplasties. However, little quantitative understanding of the debonding process, as well as of the optimum interface morphology for enhanced resistance to debonding, exists. Accordingly, a fracture-mechanics approach has been used in which adhesion at the interface is characterized in terms of the interface fracture energy, G (J/m2), and shown to be a strong function of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Whereas previous investigations have only reported critical debond values, 12,[29][30][31] this study includes the important effect of salient interface parameters such as initial surface morphology (roughness), surface precoating, cement layer thickness, physiological environment, and debond length on both critical fracture resistance and subcritical debondgrowth rate behavior. Understanding the fatigue debonding behavior in particular is a prerequisite for improved lifetime predictions of cemented systems under alternating physiological loads and provides a quantitative basis for designing interfaces with improved long-term reliability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whereas previous investigations have only reported critical debond values, 12,[29][30][31] this study includes the important effect of salient interface parameters such as initial surface morphology (roughness), surface precoating, cement layer thickness, physiological environment, and debond length on both critical fracture resistance and subcritical debondgrowth rate behavior. Understanding the fatigue debonding behavior in particular is a prerequisite for improved lifetime predictions of cemented systems under alternating physiological loads and provides a quantitative basis for designing interfaces with improved long-term reliability.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the formation of a debond bridging zone behind the debond tip, where polymer ligaments may be left behind the debond tip as the debond extends, as previously reported. 12 In addition, wear debris at the prosthetic-PMMA interface was observed [ Fig. 7(a,d)].…”
Section: Fractographymentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 The augmentation of the surface roughness or surface energy allows for developing mechanical interlock of the implant and bone cement interface, which can improve the bonding characteristics of the implant-cement interface. 8 Hosein et al 9 pointed out that circumferential-grooved stems offered improved stability under compression relative to the smooth stems. It has been revealed that porous coating of the femoral stems dramatically improved push-out strengths and fatigue properties of the stem-cement interface through increasing surface roughness.…”
Section: Introductionmentioning
confidence: 99%